M. Pincon - Charlot, E. Preteceille, P. Rendu: Segregation urbaine. Classes sociales et equipements collectifs en region parisienne - Μαλούτας Θωμάς (The Greek Review of Social Research, 1987)
[Δεν διατίθεται περίληψη / no abstract available]